Media Pembelajaran Berbantuan Komputer: Penggunaan dan Pengaruhnya Terhadap Pemahaman Konsep Matematis Siswa SMP - Meilani Safitri; Tria Gustiningsi; Lis Amalia (Teknodika, 2019)
The aim of this research is to develop mathematics learning media for student in class VII of junior high school. After going through the stages of developing a valid and practical instructional media, the instructional media is used to see whether there is an influence of its use on the understanding of mathematical concepts of grade VII junior high school students. The method used in this study is a mix method between development and experimentation. The results of this study are valid and practical learning media. While the effect on understanding students' mathematical concepts is significant. Thus, the initial hypothesis was accepted.